Síndrome de burnout en pandemia y satisfacción laboral en médicos serumistas de Ayacucho - Prado Núñez, Jesús Sebastián (2024)
Objective: To determine the association between psychosocial work factors and symptoms of anxiety or depression among healthcare personnel in the Intensive Care Unit (ICU) at Hospital Regional Eleazar Guzmán Barrón in Nuevo Chimbote. Materials and methods: An observational, cross-sectional study was conducted, using both crude and adjusted models, to determine the association between burnout syndrome (BS), evaluated through the Maslach Burnout Inventory (MBI), and job satisfaction (JS), assessed via the Job Satisfaction Questionnaire S20/23. The associations were expressed as prevalence ratios (PR) with their respective 95 % confidence intervals (95 % CI). Results: Out of the 70 doctors engaged in the SERUMS program, 77.14 % were aged between 18 and 33 years, 52.86 % were males, 51.43 % had less than one year work experience and 88.57 % worked at a health center of the Ministry of Health. The prevalence of BS was 45.71 %. The prevalence of JS was as follows: dissatisfaction 30 %, satisfaction 32.86 % and indifference 37.14 %. In the crude analysis, a statistically significant association between BS and JS was found (PR = 13.5; 95 % CI: 3.08 - 59.24) and in the analysis adjusted for sex, marital status and length of work experience, the association between BS and JS remained statistically significant (PR = 14.15; 95 % CI: 3.02 - 66.32). Conclusions: BS is negatively associated with JS, with one in two doctors experiencing BS. Moreover, there appears to be a higher likelihood of job dissatisfaction among personnel with BS. This suggests that BS could serve as an indicator in different management areas and be considered in health management decision-making. Solving these issues could contribute to improving current working conditions and, therefore, the healthcare system.